If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 8V = 6 + 3v Solving -4 + 8V = 6 + 3v Solving for variable 'V'. Move all terms containing V to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 8V = 6 + 4 + 3v Combine like terms: -4 + 4 = 0 0 + 8V = 6 + 4 + 3v 8V = 6 + 4 + 3v Combine like terms: 6 + 4 = 10 8V = 10 + 3v Divide each side by '8'. V = 1.25 + 0.375v Simplifying V = 1.25 + 0.375v
| X^2(x-3)=320 | | y=(5x-3)(2x+1) | | -6(4d+10)+7d=-3d | | 202=(4x-1)*(5x+3) | | 3(n-3)-(7-n)= | | 50.4=2.5x*(15.4+y) | | 12=7t-44 | | x+2/8=-3 | | 50.4=2.5x*(15.4+x)y | | 2y+3(y+5)= | | 50.4=2.5x*(15.4+x) | | 3x+1-2x-7=0 | | f(x)=2x^4+x^3-53x^2-14x+20 | | 10x-12=9x | | 12*k-13=39 | | 2-y=2-1 | | -5(-5+4w)=-15 | | 1=7t+8 | | 15+4k=-57 | | 2x+4+62=180 | | -20-13x=-371 | | 7+7b=35 | | -45=7-2p | | 19=23-4b | | Log(x+14)-log(x+6)=logx | | t-3=13 | | 13+7v=97 | | 3(x-7)=x-6 | | 105-3h=69 | | 6x+16=5x+9 | | 1.5(x-24)=13 | | f(-3)=6x^2-12 |